Neighbors 2 [videorecording (DVD)] - Stoller, Nicholas; Rogen, Seth, 1982-; Rogen, Seth, 1982-; Efron, Zac; Byrne, Rose; Moretz, Chloë, 1997-; Franco, Dave, 1985- (Universal Studios Home Entertainment, 2016)
Now that Mac and Kelly Radner have a second baby on the way, they are ready to make the final move into adulthood, the suburbs. Just as they thought they'd reclaimed the neighborhood and were safe to sell, they learn that the new occupants next door are a sorority even more out of control than Teddy and his brothers. Now forced to turn to the one ex-neighbor with the skills to bring down the new Greeks next door, they bring in charismatic Teddy as their secret weapon.